Analisis Sistem Penanganan Komplain di Rumah Sakit Permata Medika Semarang - Krisantus Lou Musu; Chriswardani Suryawati; Hardi Warsono (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2020)
Complaint handling becomes an important groove when the resulting product does not match the customer's expected value. Complaints can be used as an opportunity to improve and develop hospital services. This research aims to analyze the complaint handling system and identify the complaint-handling factor and formulate a good complaints handling system in Permata Medika Hospital. This research uses a qualitative approach. The results showed that the input variables: commitment to handling complaints directly responsive handled no longer than 1-2 days, the system only has Operating Procedure Standards and flow, facilities to support complaint handling are complete, there is no training, seminars and delegations, reporting once a month , follow-up on handling complaints returned to their respective units, there are Standard Operating Procedures for handling complaints both verbally and in writing. Process variable: complaint handling is done by receiving, reviewing, investigating and resolving. Output variable: complaints were resolved directly in 176 cases and 20 cases required additional investigation time out of a total of 196 cases. Obstacles identified: have not categorized complaints based on severity, no policies, duties and responsibilities and evaluation has not been conducted. Formulate a good system with transparency and complaint handling strategies.It was concluded that there was no policy input for handling complaints, there was no categorization process for handling complaints, Output: 90% of complaints cases were immediately resolved, formulating complaints handling strategies and transparency mechanisms for handling complaints. Keywords : complaints, complaint handling, complaint managementBibliography : 47 (1999-2014)